BEGONIA TJIASMANTOI, A NEW SPECIES FROM WEST SULAWESI - Wisnu Handoyo Ardi; Daniel C. Thomas (Reinwardtia, 2020)
ARDI, W. H. & THOMAS, D. C. 2020. Begonia tjiasmantoi, a new species from West Sulawesi. Reinwardtia 19(1): 61‒65. ‒‒ A new species, Begonia tjiasmantoi Ardi & D.C.Thomas is described from Mamasa, West Sulawesi, Indonesia. The species is endemic to West Sulawesi and belongs to Begonia section Petermannia. A provisional conservation assessment indicates a Critically Endangered status